SIZING AND CONSTRUCTION OF PIEZOELECTRIC VIBRATION TRANSDUCERS (ELECTRICAL MACHINES, MATERIALS AND DRIVES — PRESENT AND TRENDS, 2024)
The paper presents the construction of piezoelectric accelerometers, the mechano-electrical transfer mode, typical constructions, basic characteristics, and theoretical approaches to the vibration phenomenon appearing in accelerometry and calculation possibilities of the various characteristics of the transducers. In the second part of the paper, the functional testing of such a transducer is also presented, piezoelectric vibration transducers being useful for vibration determination and dynamic balancing of electric machines. In general, vibration transducers provide, through mechano-electrical conversion according to different principles, an electrical signal directly proportional to a vibration parameter (acceleration, travel speed, amplitude); depending on the principle, they can be piezoelectric, electrodynamic, inductive, capacitive, resistive or based on the Hall effect, with magnetic fluids, interferometric, laser, servo-accelerometers, etc. Since there is no universal accelerometer, each one is intended to encompass the characteristics of a concrete application best, the way of stressing the photosensitive medium in the first place, the design,, as well as the other characteristics,, vary from one construction to another.
Keywords: Piezoelectric transducer; Vibrations; Sizing and construction; Aplications; Testing